Prolonged versus brief balloon inflation during arterial angioplasty for de novo atherosclerotic disease: a systematic review and meta-analysis - Rockley, Mark; Jetty, Prasad; Radonjic, Aleksandar; Rockley, Kathleen; Wells, George; Fergusson, Dean (Université d'Ottawa | University of Ottawa, 2019)
Abstract Objective Angioplasty is a fundamental treatment for atherosclerotic disease and may be performed as the sole therapy in small vessel disease. However, the ideal duration of balloon inflation has not yet been identified. Our study investigated whether prolonged inflation of at least 1-min duration, when compared with brief inflation, affects residual stenosis after arterial angioplasty. Data sources and methods Two independent reviewers conducted a systematic review of EMBASE, MEDLINE, CENTRAL, trial registries and grey literature, using pre-specified search syntax. Data abstraction and quantitative analysis was performed independently, according to pre-specified criteria. The primary outcome was residual stenosis after initial angioplasty, in addition to other pre-specific clinical and radiographic outcomes. All analyses were stratified by coronary, cerebrovascular, and peripheral territory. The study protocol is published and registered on PROSPERO (CRD42018092702). Results Six relevant articles were identified, of which one investigated peripheral vascular angioplasty and five investigated coronary artery angioplasty, encompassing 1496 procedures. The studies were at moderate risk of bias. Minimal heterogeneity within coronary studies allowed for subgroup meta-analysis. Prolonged inflation was significantly associated with lower risk of residual stenosis post-inflation in the pooled coronary trials (RR 1.76 [95% CI 1.46–2.12], I2 = 0%, p < 0.001) in addition to approaching significance in the peripheral vascular trial (RR 2.40 [95% CI 0.94–6.13], p = 0.07). Prolonged inflation was associated with less risk of arterial dissection and need for adjunctive procedures such as stenting. Following adjunctive procedures, less residual stenosis was still observed in the prolonged angioplasty group in the reported coronary studies. Follow-up data did not reveal a significant difference in the presence of restenosis, however there was a long-term benefit of prolonged inflation in reducing overall severity of stenosis. Discussion This is the first review investigating outcomes related to duration of balloon inflation. Both coronary and peripheral vascular evidence are in agreement that prolonged angioplasty balloon inflation greater than 60 s appears to be associated with improved immediate post-inflation results. However, long-term data is heterogeneous and inconsistently reported. We propose further investigation to address outstanding long-term outcomes, particularly in small vessel territories such as tibial vessels where angioplasty is often used as the only endovascular therapy. Trial registration This protocol has been registered with the International Prospective Register of Systematic Reviews (PROSPERO: CRD42018092702 ) prior to conduct of the review.